The Effect Of Information Technology Sophistication, Internal Control, Top Management Support And Innovative Culture On The Quality Of Accounting Information Systems - Siti Andra Wulan; Bobby Fisher (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
In the digital era, the quality of accounting information systems is an urgent need to support effective decision making. This study aims to analyse the effect of information technology sophistication, internal control, top management support, and innovative culture on the quality of accounting information systems. This research uses a quantitative method with a survey involving 96 respondents from various companies. Data were collected through questionnaires and analysed using SEM-PLS. The results showed that the sophistication of information technology and innovative culture had a significant effect on the quality of accounting information systems. In contrast, internal control and top management support showed no significant effect. In addition, innovative culture cannot mediate the relationship between top management support and accounting information system quality. These findings provide new insights into the importance of implementing modern technology and innovative culture to improve the quality of accounting information. In conclusion, companies need to focus on technological innovation and organisational culture to ensure reliable accounting information systems.